SOME ISSUES OF USING INTERNET RESOURCES IN THE DEVELOPMENT OF STUDENTS’ RESEARCH ACTIVITIES - Issabaeva Д.; Sadirbekova Д.; Nishanbaeva, C.; Aitenova Э. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
This article presents a systematic review of the literature on the impact of Internet resources and digital technologies on students’ educational and research activities. The study is based on an analysis of scientific articles, international conferences, and the results of a survey of students and teachers. The article’s main conclusions emphasize that digital technologies and Internet resources play a significant role in the modern educational process. Students have a unique opportunity to access a wealth of information and develop research skills. However, despite these benefits, students often face difficulties assessing the quality of information in the digital environment and information overload. Educators play an important role in developing digital skills by teaching students not only how to use technology, but also how to evaluate information and use a variety of sources. Students should learn a variety of information retrieval techniques, including the use of databases, reputable news sources, and printed materials. Additionally, the article highlights the importance of developing patience and time management skills when working with digital resources. Overall, the study highlights the need to develop information skills among students and the active role of educational institutions and teachers in this process. Effective use of digital resources requires a balance between the availability of information and the ability to assess its quality in the modern digital educational environment.